Investigating the Use of Wastewater Sludge-Based Fuels - Emmanuel Owino (Uganda Christian University, 2024)
This study examines the potential of wastewater sludge-based fuels through hydrothermal carbonisation, a process of converting biomass into carbonaceous material under elevated temperature and pressure in a closed system. The investigation aims to utilize wastewater sludge from the UCU Wastewater treatment plant as a biofuel, focusing on determining its properties as a suitable feedstock, optimizing process conditions for maximum hydrochar yield and briquette formation, evaluating the fuel characteristics of the resulting briquettes, and conducting a cost- benefit analysis. Proximate analysis, calorimetry, water boiling tests, and AHP analysis were employed. Optimal conditions were found at 230°C with 50% moisture content for 2 hours, yielding a heating value of 14.89 MJ/kg. Briquettes composed of 15% starch, 5% sand, and 80% hydrochar exhibited favourable properties, although reactor instability at high moisture content levels suggests the need for a stirred hydrothermal reactor. Further research to enhance briquette water resistance is recommended to improve durability for diverse applications.